Study of Physical Treatment of Cuttings on the Production of Cassava (Manihot esculenta Crantz) - Stevani B Fara; Fitri Wahyu Wijayanti; Astri Djuhaery (Agrologia, 2019)
Tuber of Cassava (Manihot esculenta Crantz) is a source of food and industrial raw materials. The purpose of this study was to examine the effect of physical treatment of cuttings on the production of cassava plants. The treatment that was tried was the physical treatment of cuttings, by being tapered, chopped, scraped, and tapered and without treatment as a control. The study used a randomized block design with four replications. The responses observed were the number and weight of tubers, and the carbohydrate content. The results showed that the physical treatment of cuttings affected the number and weight of tubers, but did not affect the carbohydrate content. The highest number of tubers and the weight of tubers is found in the tubers of the plant with tapered cuttings. The average low number and weight of tubers from plants which were treated physically on cuttings and controls compared with the physical treatment of tapered cuttings was 40.54% number tuber and 48.35% weight tuber. The average carbohydrate content is 29.62%.Keywords: Cassava, cuttings, Manihot esculenta, production